Landslide Susceptibility Mapping and Their Rainfall Thresholds Model in Tinalah Watershed, Kulon Progo District, Yogyakarta Special Region, Indonesia - Thema Arrisaldi; Wahyu Wilopo; Teuku Faisal Fathani (Geological Engineering Department Universitas Gadjah Mada, 2021)
Landslide often occurred in Tinalah watershed, Kulon Progo District, every year. The frequency of landslide events is increasing after high rainfall intensity. Some factors control landslides such as slope gradient, land use, geological structure, slope hydrology, and geological condition. This research has an objective to develop the susceptibility map of Tinalah watershed and to identify the rainfall threshold to trigger a landslide. The development of the susceptibility map using frequency ratio method with four parameters including slope, type of rock, land use, and lineament density. The landslide data were collected during the field survey and from regional disaster management authority (BPBD) Kulon Progo. Rainfall data were collected from BMKG and GSMap. Soil analysis also was conducted to develop a numerical model to verify the rainfall threshold value. The result shows a high susceptibility of the landslide area is dominated in Tinalah watershed. The rainfall threshold for the low susceptibility of the landslide zone is I=490.14 D-1.404with 5-7 days antecedent rain. The rainfall threshold for medium susceptibility map is I=164.32D-0,689 3-7 days antecedent rain. Moreover, the rainfall threshold for the high susceptibility of the landslide zone is 111.62 D-0.779, with 2-7 days antecedent rain.